Strategies and challenges for green campuses - Barnett-Itzhaki, Zohar; Tifferet, Sigal; Berkowic, Daniel; Arviv, Tamir; Daya, Alon; Carasso Romano, Gal Hagit; Levi, Adi (Frontiers in Sustainable Cities, 2025)
The global environmental and ecological climate crisis necessitates urgent mitigation and adaptation measures, with Higher Education Institutions (HEIs) playing a crucial role in driving the transition toward a sustainable future. This paper examines the dual approach HEIs can adopt to foster sustainability: educating future generations and implementing green campus initiatives that can serve as models for the broader community. This review synthesizes existing research and case studies, identifies key areas for sustainability efforts within HEIs and analyzes the barriers and potential solutions for implementing sustainable practices on campuses. The broad range of areas include energy efficiency and renewable production, emissions mitigation, water and waste management, sustainable buildings and laboratories, and eco-friendly landscaping. The synthesis of findings revealed that HEIs can function as microcosms of sustainable urban environments, showcasing efficient resource management and infrastructure enhancement. Additionally, it highlighted the various actions HEIs should take to achieve campus sustainability. The major actions include establishing a dedicated Sustainability Office to coordinate efforts and set measurable goals; Implementing environmental initiatives (such as energy conservation and waste reduction); Engaging all campus stakeholders through education and participation in sustainability programs; Adopting standardized practices for resource management; Securing strong leadership support and funding; Fostering collaboration and innovation across disciplines and extending impact beyond campus to inspire environmental stewardship in the broader community. By implementing these actions HEIs can make significant strides toward campus sustainability, while significantly strengthening local and global mitigation efforts of climate change, pollution and biodiversity loss.